Mengeliminasi Politik Uang pada Pemilih Muda melalui Pendekatan Hukum dan Agama - Firmansyah, Firmansyah; Iderus, Muhammad Hasan Said; Syarifudin, Ahmad; Sudirman, Sudirman; Septiani, Dini Lionita; Furyani, Sri (DEDIKASI: Jurnal Pengabdian Masyarakat, 2024)
Young voters in Lampung Province still tend to show a permissive attitude towards the practice of money politics, especially leading up to the 2024 General Election. One of the main factors is the lack of adequate understanding of money politics among young voters. Previously, it was identified that legal and religious approaches could be a solution to address this issue. In this community service activity, we applied previous research findings using the service learning method to reduce the practice of money politics among young voters in Lampung Province. This approach includes aspects of Indonesian positive law and Islamic law. We used a mono-disciplinary service learning type that involved several stages, such as planning, preparation, implementation, evaluation, reflection, and further development. After going through the stages of activities in the service, the results were quite satisfying. Based on a survey at the end of the activity, it was found that young voters had gained sufficient knowledge regarding money politics and had changed their attitude from permissive to rejecting all forms of money politics